2012
DOI: 10.1136/jmedgenet-2011-100586
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer susceptibility polymorphisms: confirmation of loci on chromosomes 9q22 and 14q13, validation of a recessive 8q24 locus and failure to replicate a locus on 5q24

Abstract: Five single nucleotide polymorphisms (SNPs) associated with thyroid cancer (TC) risk have been reported: rs2910164 (5q24); rs6983267 (8q24); rs965513 and rs1867277 (9q22); and rs944289 (14q13). Most of these associations have not been replicated in independent populations and the combined effects of the SNPs on risk have not been examined. This study genotyped the five TC SNPs in 781 patients recruited through the TCUKIN study. Genotype data from 6122 controls were obtained from the CORGI and Wellcome Trust Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
102
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 18 publications
12
102
1
Order By: Relevance
“…Two SNPs that showed highly significant association with PTC were detected (rs965513 and rs944289). The variants were located in 9q22.33 and 14q13.3, respectively, and have been confirmed by other research groups (14,15). As both SNPs were located in gene-poor regions, no immediate candidate genes presented themselves as being affected by or associated with the risk alleles of the SNPs.…”
supporting
confidence: 69%
“…Two SNPs that showed highly significant association with PTC were detected (rs965513 and rs944289). The variants were located in 9q22.33 and 14q13.3, respectively, and have been confirmed by other research groups (14,15). As both SNPs were located in gene-poor regions, no immediate candidate genes presented themselves as being affected by or associated with the risk alleles of the SNPs.…”
supporting
confidence: 69%
“…The same study revealed that tumor DNA of up to 6% of patients undergoes somatic mutations within rs2910164, which additionally confirmed the role of this variant in the pathogenesis of PTC (26). The rs2910164-mediated predisposition was further analyzed in 781 thyroid cancer patients recruited in the United Kingdom (28), and the study revealed no association between the polymorphism and thyroid cancer risk. Similar results were obtained in 753 Chinese patients (29) and in 307 Italian patients (30).…”
Section: Microrna-mediated Thyroid Cancer Riskmentioning
confidence: 77%
“…8 (4). The association between rs965513 and thyroid cancer risk has been independently confirmed in different populations (5)(6)(7)(8)(9)(10)(11). The association was also observed in familial PTC and in patients with radiation-induced PTC (12)(13)(14)(15).…”
mentioning
confidence: 70%
“…To assess SNPs across the 9q22 locus and to identify functional SNPs, as well as additional associated variants that may contribute to PTC predisposition, we performed targeted next-generation sequencing in a gene-poor region of about 167 kb [genomic coordinates chromosome 9: 100455000-100622000 (GRCh37/hg19)] on DNA from 22 patients with PTC, including 10 [AA], 6 [AG], and 6 [GG] genotypes of the lead SNP rs965513. The region contains both coding genes (XPA and FOXE1) that flank the lead SNP.…”
Section: Resultsmentioning
confidence: 99%